Electrical properties of calcium doped BiFeO3 films on LaNiO3 coated Pt substrates - Goncalves, L. F. [UNESP]; Rocha, L. S. R. [UNESP]; Hangai, B. [UNESP]; Silva Ortega, Pedro Paulo [UNESP]; Longo, E. [UNESP]; Simoes, Alexandre Z. [UNESP] (Univ Novi Sad, Fac Technology, 2018)
Pure and calcium-modified (CaxBi1-xFeO3, x = 0.0, 0.1, 0.2, 0.30) thin films were fabricated on Pt(111)/Ti/SiO2/Si substrates by the soft chemical method using LaNiO3 as the bottom electrode. Highly (200)-oriented BFO film was coherently grown on LNO at 500 degrees C. Ca-doped BiFeO3 films have a dense microstructure and rounded grains. The conventional problem of the leakage current for the highest doped film was reduced from 10(-5) to 10(-10) with remarkable improvement in the film/electrode interface, chemical homogeneity, crystallinity, and morphology of the BFO film. Enhanced ferroelectricity was observed at room temperature due to the bottom electrode. Fatigue-free films were grown on LaNiO3 bottom electrodes with no degradation after 1x10(10) switching cycles at an applied voltage of 5 V with a frequency of 1 MHz. After several tests the capacitors retained 77% of its polarization upon a retention time of 10(4) s. Room temperature magnetic coercive field measurements indicate that the magnetic behaviour is influenced by the nature of the bottom electrode.
Keywords: bismuth ferrite; multiferroics; lanthanum nickelate; thin films